Investigation of aPandoraea apistacluster common to adult and paediatric cystic fibrosis patients attending two hospitals in the same city. Issue 7 (July 2019) - Kenna, Dervla T. D.; Coward, Amy; Perry, Claire; Pike, Rachel; Schaefer, Ulf; Turton, Jack; Green, Heather; Jones, Andrew M.; Bright‐Thomas, Rowland J.; Burns, Phillipa; Narayan, Omendra; Wilkinson, Stuart; et al.
Abstract : Abstract : Purpose. We examined evidence for transmission of Pandorea apista among cystic fibrosis (CF) patients attending paediatric and adult services in one city who had previously been found to harbour related isolates by pulsed‐field gel electrophoresis (PFGE). Methodology. The whole‐genome sequences of 18 isolates from this cluster from 15 CF patients were examined, along with 2 cluster isolates from 2 other centres. The annotated sequence of one of these, Pa14367, was examined for virulence factors and antibiotic resistance‐associated genes in comparison with data from a 'non‐cluster' isolate, Pa16226. Results. Single‐nucleotide polymorphism (SNP) analysis suggested that cluster isolates from the same city differed from one another by a minimum of 1 and a maximum of 383 SNPs (an average of 213 SNPs; standard deviation: 18.5), while isolates from the 2 other hospitals differed from these by a minimum of 34 and 61 SNPs, respectively. Pa16226 differed from all cluster isolates by a minimum of 22 706 SNPs. Evidence for patient‐to‐patient transmission among isolates from the same city was relatively limited, although transmission from a common source could not be excluded. The annotated genomes of Pa14367 and Pa16226 carried putative integrative and conjugative elements (ICEs), coding for type IV secretion systems, and genes associated with heavy metal degradation and carbon dioxide fixation, and a wide selection of genes coding for efflux pumps, beta‐lactamases and penicillin‐binding proteins. Conclusion. Epidemiological analysis suggested that this cluster could not always be attributed to patient‐to‐patient transmission. The acquisition of ICE‐related virulence factors may have had an impact on its prevalence.